Application of Organic Fertilizer POC (Rice Washing Water) and Cow Manure on The Growth and Yield of Bird's Chili (Capsicum Frutescens L) Plants - Made Sri Yuliartini; Desak Ketut Tristiana Sukmadewi; I Gusti Ngurah Yogi Iswara Wibawa (Agriwar Journal, 2025)
This study aims to determine the effect of liquid organic fertilizer (POC) application from rice water washing and cow manure on the growth and yield of cayenne pepper (Capsicum frutescens L). The method used is a Randomized Block Design (RBD) with two treatment factors, namely the concentration of POC (10 cc.l -1, 20 cc.l -1, and 30 cc. l ---1) and the dose of cow manure (10 tons ha -1, 15 tons ha -1-, and 20-tons ha -1). The results of the analysis showed that the interaction between the concentration of POC and the dose of cow manure did not have a significant effect (P>0.05) on all observed variables. The treatment of rice water washing POC concentration gave the highest fresh weight of fruit bunches at a concentration of POC (C3) 30 cc.l -, namely 44.18 g, or an increase of 6.4% from the lowest fresh weight of fruit bunches obtained at a concentration of POC (C1) 10 cc.l-1, namely 40.19 g, the highest oven dry weight of fruit bunches at a concentration of POC 30 (C3) cc.l-1, namely 10.49 g, an increase of 28.5%. The treatment of cow manure dose had no significant effect (P>0.05) on all observed variables. There was a significant effect on the number of harvested fruits per plant, where the treatment of POC 30 cc.l -1 and the dose of cow manure 30 tons ha -1. This study concluded that the use of liquid organic fertilizer (POC) from rice washing water and cow manure can increase cayenne pepper yields, although the effect varies depending on the variables observed. It is hoped that these results will provide useful information for farmers in sustainably increasing cayenne pepper productivity.